(untitled) (Research, Society and Development, 2022)
This article addresses the non-epileptic seizure in paroxysmal events of psychogenic origin. It discusses the difficulties that health professionals, responsible for the diagnosis, have when dealing with individuals who present epileptic signs and symptoms, but which, in turn, are not related to epilepsy. In this context, we investigate the process of diagnosing Non-Epileptic Psychogenic Crisis (NCNE). For this, the bibliographic research was used as a methodological procedure. During this process, data was collected from published articles that covered and portrayed the theme directed to clinical practice, thus, academic publications were analyzed, those of interest were selected, and through observation, the data were analyzed in order to gather the knowledge produced. About the subject. After research, it was concluded that it is necessary for health teams to be aware of the characteristics, diagnosis and treatment of a PNEC, so that, in the face of any apparent occurrence, they seek to investigate, in detail, the individual’s life history and that, in sequence, the patient is referred to the video-electroencephalogram, in order to correctly discard or confirm the investigation and offer a resolutive treatment.